Contingent claims analysis of sovereign debt sustainability in Asian emerging markets - Marie Brière; Benno Ferrarini; Arief Ramayandi (Asian Development Bank (ADB), 2016)
Contingent claims analysis applied to Indonesia, Malaysia, the Philippines, the Republic of Korea, and Thailand shows no particular vulnerability to sovereign debt distress during recent years. However, the highly volatile "distance to distress" measure suggests that any of these countries may fall victim to a sudden loss in market confidence. For example, the value of Indonesia's sovereign assets dropped to just two standard deviations above its repayment obligations during the 2013 Fed taper tantrum, causing capital outflows and currency depreciation. Generally, we find that contingent claims analysis and market-based risk measures well complement conventional debt sustainability analysis for Asia.
Keywords: E60; F34; G13; H63; 330; contingent claims analysis; public debt sustainability